ANALYSIS OF ANTEROFRONTAL AND TEMPOROPARIETAL INTERHEMISPHERIC BRAIN WAVE ACTIVITY FROM POST FLOOD DISASTER VICTIMS THROUGH INTERVIEW-BASED EEG MEASUREMENTS - Syahidah, Shofa
Negative experiences (unpleasant events) due to floods can disrupt the psychological condition of individuals that trigger chronic stress. Stimulation of stress due to floods induces brain wave activity in the brain hemisphere area which can be measured physiologically in the form of brain waves by electroencephalograph (EEG) devices. This study aims to determine the theta and gamma brain wave activity with EEG devices through an interview approach that includes the baseline (control), recall, and resolution phases of 11 inmates (aged 36-53 years, male = 6, female = 5). ), who was a victim of the flood disaster in Mulyasari Village, Pamanukan District, Subang Regency. Outcome data are anti-logarithmic Power Spectral Density (PSD) of two lobes: anterofrontal (AF7 and AF8), and temporoparietal (TP9 and TP10). The results showed (a) increased activity of the AF and TP area theta waves in the recalling phase (b) increased TP area gamma waves and decreased AF area gamma waves in the recalling phase (p < 0.05). Comparison of interhemispheric brain wave activity showed significant differences in interhemispheric activity in theta and gamma AF lateralized in the left hemisphere and gamma TP lateralized in the right hemisphere (p < 0.05). The correlation test results showed a significant correlation of theta-gamma wave activity in the recalling phase (p < 0.01) and resolution (p < 0.05) in the temporoparietal area. The results also showed significant differences in theta and gamma wave activity based on gender differences where the theta AF8 and TP9 as well as gamma AF7, TP9, and TP10 brain wave activity was higher in male subjects and the theta wave activity was AF8 and TP10 and gamma in the channel. AF8 was more dominant in female subjects (p < 0.05). while the theta and gamma wave activity in the AF and TP areas elicited a stress response indicated from the activation of these two areas induced from the interview questions. Meanwhile, in male subjects, the theta and gamma wave activity was more dominant in the left hemisphere, whereas in female subjects, theta and gamma wave activity was more dominant in the right hemisphere. Characteristics of theta and gamma wave activity on male subjects that lead to problems related to unpleasant stimuli and on female subjects whose completion and decreased impulsive responses. It can be ascertained that the characteristics of theta and gamma wave activity in the recall phase have negative memories and emotions in the form of anxiety related to the flood experience.